Raising Awareness of IT Regulations and Compliance through Symposium on Philippine Public High Schools in Buenavista, Guimaras - Tamdang, Divon; Borreros, Alfred John; Forca, Adrian (Jurnal Pengabdian Masyarakat Inovatif, 2024)
This study focused on Raising Awareness of IT Regulations and Compliance of Philippine Public High Schools in Buenavista, Guimaras through a symposium as tool to measure the awareness level. With the aim of educating, discussing, and collaborating the effective implementation of the law on RA 10175 and address concerns and highlight practices to promote digital practices in living in the IT Era. The researchers made use of the standard instrument relative to the community extension services and result shows that there is a significant improvement in terms of the level of awareness. There were 194 participants responded and general, the researchers identified that significant contribution that 40 out of 194 or 20.61% responses have acquired knowledge and skills above 3 or Some knowledge and skills in RA 10175. The symposium was a success, achieving its objectives of educating and engaging the participants on the critical issue of cybercrime prevention